Beyond the hype: how the Metaverse can revolutionize higher learning in an authentic way / Mia Emily Abdul Rahim and Emma Marini Abdul Rahim - Abdul Rahim, Mia Emily; Abdul Rahim, Emma Marini (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Many of us have heard of the Metaverse, but only a handful have genuinely experienced it. Coined by the famous science fiction author Neal Stephenson, the Metaverse refers to a virtual space where people can interact with each other through their avatars in a 3D environment. This technology has gained popularity in recent years, thanks to augmented reality (AR), virtual reality (VR), and extended reality (XR) platforms' development. In the education sector, Metaverse-based applications can be incorporated with face-toface learning, creating a truly authentic English learning environment for learners. English as a second language (ESL) learners can use the Metaverse to practice their language skills in a fun and interactive way.